Endoplasmic Reticulum Aminopeptidase 1 Is Involved in Anti-viral Immune Response of Hepatitis B Virus by Trimming Hepatitis B Core Antigen to Generate 9-Mers Peptides - Liu, Huanhuan; Hu, Bingqi; Huang, Junfeng; Wang, Qin; Wang, Feier; Pan, Faming; Chen, Liwen (Frontiers in Microbiology, 2022)
Endoplasmic reticulum aminopeptidase 1 (ERAP1) is a processing enzyme of antigenic peptides presented to major histocompatibility complex (MHC) class I molecules. ERAP1-dependent trimming of epitope repertoire determines efficacy of adoptive CD8+ T-cell responses in several viral diseases; however, its role in hepatitis B virus (HBV) infection remains unknown. Here we show that the serum level of ERAP1 in chronic hepatitis B (CHB) patients (n=128) were significantly higher than that of healthy controls (n=44) (8.78±1.82 vs. 3.52±1.61, P<0.001). Furthermore, peripheral ERAP1 level was moderately correlated with HBV DNA levels in CHB patients (r=0.731, P<0.001). HBV-transfected HepG2.2.15 cells had substantially increased ERAP1 expression than the germ line HepG2 cells (P<0.001). The co-culture of ERAP1 specific inhibitor ERAP1-IN-1 pretreated HepG2.2.15 cells with CD8+ T cells led to 14%-24% inhibition of the proliferation of CD8+ T cells. Finally, liquid chromatography tandem mass spectrometry (LC-MS/MS) test demonstrated that ERAP-IN-1 produce a complete block of 9-mers (30-38, LLDTASALY) derived from HBcAg. The predictive analysis by NetMHCpan-4.1 server showed that HLA-C*04:01 is a strong binder for the 9-mers peptide in HepG2.2.15 cells. Taken together, our results demonstrated that ERAP1 trims HBcAg to produce 9-mers LLDTASALY peptide for binding onto HLA-C*04:01 in HepG2.2.15 cells, facilitating potential activation of CD8+ T cells. As a primary goal, the abstract should render the general significance and conceptual advance of the work clearly accessible to a broad readership.